TNFR1-d2 carrying the p.(Thr79Met) pathogenic variant is a potential novel actor of TNFα/TNFR1 signalling regulation in the pathophysiology of TRAPS - Cécile Rittore; Déborah Méchin; Elodie Sanchez; Léa Marinèche; Vuthy Ea; Stephan Soler; Marion Vereecke; Aude Mallavialle; Eric Richard; Isabelle Duroux-Richard; Florence Apparailly; Isabelle Touitou; et al. (Scientific Reports, 2021)
Abstract Binding of tumour necrosis factor α (TNFα) to its receptor (TNFR1) is critical for both survival and death cellular pathways. TNFα/TNFR1 signalling is complex and tightly regulated at different levels to control cell fate decisions. Previously, we identified TNFR1-d2, an exon 2-spliced transcript of TNFRSF1A gene encoding TNFR1, whose splicing may be modulated by polymorphisms associated with inflammatory disorders. Here, we investigated the impact of TNFRSF1A variants involved in TNFR-associated periodic syndrome (TRAPS) on TNFR1-d2 protein expression and activity. We found that TNFR1-d2 could be translated by using an internal translation initiation codon and a de novo internal ribosome entry site (IRES), which resulted in a putative TNFR1 isoform lacking its N-terminal region. The kinetic of assembly of TNFR1-d2 clusters at the cell surface was reduced as compared with full-length TNFR1. Although co-localized with the full-length TNFR1, TNFR1-d2 neither activated nuclear factor (NF)-κB signalling, nor interfered with TNFR1-induced NF-κB activation. Translation of TNFR1-d2 carrying the severe p.(Thr79Met) pathogenic variant (also known as T50M) was initiated at the mutated codon, resulting in an elongated extracellular domain, increased speed to form preassembled clusters in absence of TNFα, and constitutive NF-κB activation. Overall, TNFR1-d2 might reflect the complexity of the TNFR1 signalling pathways and could be involved in TRAPS pathophysiology of patients carrying the p.(Thr79Met) disease-causing variant.